Cathepsin-B inhibitor CA-074 attenuates retinopathy and optic neuritis in experimental autoimmune encephalomyelitis induced in SJL/J mice - Mohammad Rashid Khan; Sheikh Fayaz Ahmad; Ahmed Nadeem; Faisal Imam; Naif O. Al-Harbi; Mohd Shahnawaz Khan; Meshal Alsahli; Khaled Alhosaini (Elsevier, 2023)
The complicated multiple sclerosis (MS) can exhibit subacute sight deterioration and can lead to total deprivation of vision. In the current work, we explored the therapeutic outcome of Cathepsin B inhibitor (CA-074) against retinopathy and optic neuritis (ON) caused by experimental autoimmune encephalomyelitis (EAE) induced by proteolipid protein peptide (PLP) in female SJL/J mice. A daily dose of 10 mg/kg CA-074 was administered to the EAE mice intraperitoneally for 14 days from day 14 post-immunization until day 28. The Western blot and immunofluorescence analyses show inflammation in the optic nerve through the elevation of iNOS and NFkB markers in EAE mice. Optic neuritis was reported which is a consequence of demyelination and axon injury, estimated with the reduction in myelin basic protein (MBP). The glial fibrillary acidic protein (GFAP) expression level was found to be elevated in the retina of EAE mice which confirmed the retinopathy. The administration of CA-074 ameliorated optic neuritis and retinopathy by reducing inflammation. The treatment with CA-074 also reduced the demyelination and axonal injuries in the EAE mice. The findings of this study have shown the protective effect of CA-074 in the case of retinopathy and ON inflicted by EAE in SJL/J mice.